Gasless submental-transoral combined approach endoscopic thyroidectomy: a new surgical technique - Jiang, Jinxi; He, Gaofei; Chu, Junjie; Li, Jianbo; Lu, Xiaoxiao; Jiang, Xianfeng; Xie, Lei; Gao, Li; Zhang, Deguang (Frontiers in Oncology, 2023)
Background The development of transoral endoscopic vestibular approach thyroidectomy (TOETVA) has been limited by inherent defects, such as mental nerve injury and carbon dioxide (CO2)-related complications. Herein, we proposed a new technique without CO2 called gasless submental-transoral combined approach endoscopic thyroidectomy (STET) to solve the problems in TOETVA. Methods We reviewed 75 patients who successfully underwent gasless STET using novel instruments at our institution from November 2020 to November 2021. A main incision of approximately 2 cm was made in the natural submental crease line and then combined with two vestibule incisions to complete the procedure. Demographic data, surgical technique and perioperative outcomes were retrospectively recorded. Results Thirteen male and sixty-two female patients with a mean age of 34.0 ± 8.1 years were enrolled in this study. Sixty-eight patients had papillary thyroid carcinomas and seven had benign nodules. We successfully performed all gasless STET without conversion to open surgery. The average postoperative hospital stay was 4.2 ± 1.8 days. One transient recurrent laryngeal nerve injury and two transient hypoparathyroidisms were observed. Three patients complained of slight lower lip numbness on the first postoperative day. One case of lymphatic fistula, subcutaneous effusion, and incision swelling occurred each, all of which were conservatively cured. One patient developed a recurrence six months after surgery. Conclusions Gasless STET using our own designed suspension system is technically safe and feasible with reasonable operative and oncologic results.